New Mediterranean Biodiversity Records (November, 2016) - CH. MYTILINEOU; E.H.Kh. AKEL; N. BABALI; P. BALISTRERI; M. BARICHE; Y.Ö. BOYACI; L. CILENTI; C. CONSTANTINOU; F. CROCETTA; M. ÇELİK; H. DERELI; C. DOUNAS; et al. (Mediterranean Marine Science, 2016)
In the present Collective Article information on 26 taxa belonging to 8 Phyla and extended from the western Mediterranean to the Levantine Sea are presented. The new records were found in 9 countries as follows: Spain: first record for the Mediterranean of the crab Cancer bellianus; Algeria: further records of the alien fish Lagocephalus sceleratus to the west Algerian waters; Italy: first report on the presence and establishment of the ctenophore Mnemiopsis leidyi in Lessina and Varano Lagoons (W. Adriatic) and of Penaeus aztecus in Corigliano Gulf (Italian Ionian). Moreover, the extension of the distribution range of the polychaete Branchiomma bairdi to W. Sicily as well as that of the crab Ocypode cursor and the bryozoan Catenicella paradoxa to E. Sicily are cited. Slovenia: the record of the rare saccoglossan gastropod Placida cremoniana from Piran (Gulf of Trieste) is the first for the Adriatic; Greece: the native sea slug Eubranchus farrani is the first from the Eastern Mediterranean; many sightings of the bamboo corals Isididae distributed along all the E. Ionian Sea and the establishment of P. aztecus in all Greek waters are also reported for first time; the westernmost extension of the alien urchin Diadema setosum in Cretan waters is cited and new sights of the alien species Goniobranchus annulatus and Pterois miles are shown. Turkey: the alien fish Champsodon capensis is reported for first time from the Aegean Sea and the native acari Agauopsis microrhyncha from the Levantine Sea; a new observation of the alien crab Atergatis roseus in Güllük Bay-Aegean is also mentioned; Cyprus: first records of the alien urchin D. setosum and Lobotes surinamensis in Cypriot waters; Lebanon: several sightings of Monachus monachus from the Lebanese waters indicate a potential better status of the species in the area, Egypt: first records of the alien crab Dorippe quadridens and the alien gastropods Nerita sanguinolenta and Conomurex persicus from the Mediterranean Egyptian waters; extension of the distribution range of Diodora funiculata and Diodora rueppellii and a second record of the alien Nerita sanguinolenta in the same area.

Genetic diversity of the imperilled bath sponge Spongia officinalis Linnaeus, 1759 across the Mediterranean Sea: patterns of population differentiation and implications for taxonomy and conservation - T. DAILIANIS; C. S. TSIGENOPOULOS; C. DOUNAS; E. VOULTSIADOU (Molecular Ecology, 2011)
The Mediterranean bath sponge Spongia officinalis is an iconic species with high socio‐economic value and precarious future owing to unregulated harvesting, mortality incidents and lack of established knowledge regarding its ecology. This study aims to assess genetic diversity and population structure of the species at different geographical scales throughout its distribution. For this purpose, 11 locations in the Eastern Mediterranean (Aegean Sea), Western Mediterranean (Provence coast) and the Strait of Gibraltar were sampled; specimens were analysed using partial mitochondrial cytochrome oxidase subunit I (COI) sequences, along with a set of eight microsatellite loci. According to our results (i) no genetic differentiation exists among the acknowledged Mediterranean morphotypes, and hence, S. officinalis can be viewed as a single, morphologically variable species; (ii) a notable divergence was recorded in the Gibraltar region, indicating the possible existence of a cryptic species; (iii) restriction to gene flow was evidenced between the Aegean Sea and Provence giving two well‐defined regional clusters, thus suggesting the existence of a phylogeographic break between the two systems; (iv) low levels of genetic structure, not correlated to geographical distance, were observed inside geographical sectors, implying mechanisms (natural or anthropogenic) that enhance dispersal and gene flow have promoted population connectivity; (v) the genetic diversity of S. officinalis is maintained high in most studied locations despite pressure from harvesting and the influence of devastating epidemics. These findings provide a basis towards the effective conservation and management of the species.

Mediterranean Lagoons Revisited: Weakness and Efficiency of the Rapid Biodiversity Assessment Techniques in a Severely Fluctuating Environment - C. Arvanitidis; G. Atzigeorgiou; D. Koutsoubas; C. Dounas; A. Eleftheriou; P. Koulouri (Biodiversity and Conservation, 2005)